"I'M OPENING MY ARMS RATHER THAN PUSHING AWAY:" PERCEIVED BENEFITS OF A MINDFULNESS‐BASED INTERVENTION AMONG HOMELESS WOMEN AND YOUNG CHILDREN. Issue 3 (2nd May 2017) - Alhusen, Jeanne L.; Norris‐Shortle, Carole; Cosgrove, Kim; Marks, Lauren
ABSTRACT: Family homelessness is associated with adverse outcomes in mothers and their young children. Evidence‐based programs are needed to support the socioemotional needs of these families. The purpose of this qualitative study was to explore the perceived benefits of participating in a mindfulness program in mother–child dyads receiving services at a therapeutic nursery serving homeless children under the age of 3 years. A convenience sample of 17 predominantly African American mothers participated in in‐depth qualitative interviews. Four themes were derived from the data regarding the perceived benefits of the mindfulness program: "me" time, maternal self‐regulation, dyadic connectedness, and child well‐being. Results demonstrate the perceived benefits of mindfulness on the parent–child relationship and have important implications for families at an increased risk of adverse outcomes. Because homelessness and residential instability confer considerable risk for young children, interventions to support effective parenting are critical.